2022
DOI: 10.3389/fvets.2022.1045785
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the morphology of the anterior cruciate ligament and related bony structures between pigs and humans

Abstract: IntroductionPigs are widely used for clinical research on the anterior cruciate ligament (ACL) because of the similarity of the knee structure to the human knee. But evidence to support the suitability of using porcine samples to guide clinical practices is limited. This study aims to explore the qualitative and quantitative morphological features of the porcine knee and ACL, and to compare these with data on humans reported in literature.MethodsNineteen porcine knees were used for this study. The bone structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Porcine tissue was used and thus only partially reflects the reality in human tissue. However, anatomical and biomechanical studies have shown great similarities between pigs and human ACL and are preliminary used as xenotransplantation in humans [9,18,22]. Further, ACLs were detached from the femoral insertion using a scalpel, which does not represent rupture mechanisms in real life, potentially affecting the results.…”
Section: Limitationsmentioning
confidence: 99%
“…Porcine tissue was used and thus only partially reflects the reality in human tissue. However, anatomical and biomechanical studies have shown great similarities between pigs and human ACL and are preliminary used as xenotransplantation in humans [9,18,22]. Further, ACLs were detached from the femoral insertion using a scalpel, which does not represent rupture mechanisms in real life, potentially affecting the results.…”
Section: Limitationsmentioning
confidence: 99%
“…Dogs, which are, in veterinary praxis, often patients with ACL rupture, are also sometimes used for experimental studies [59,60]. In view on these models, one should be aware of substantial species differences in the ACL anatomy, e.g., two anteriorly completely separately attaching anteromedial and posterolateral bundles in the porcine, caprine and sheep ACL models and larger dimensions of the pig ACL compared to that of humans [60][61][62]. Bascunan et al concluded, based on their helpful review of comparative ACL anatomy and comparative biomechanical aspects, that the caprine and porcine models might show the closest similarity with human conditions [60].…”
Section: Acl Animal Modelsmentioning
confidence: 99%